Hydrodynamics of a Rising Oil Droplet With Bacterial Extracellular Polymeric Substance (EPS) Streamers Using a Microfluidic Microcosm - White, Andrew R.; Jalali, Maryam; Sheng, Jian (Frontiers in Marine Science, 2020)
During the Deepwater Horizon oil spill, the unprecedented injection of millions of liters of chemical dispersant at the wellhead generated large quantities of submillimeter oil droplets that became entrained in a deep sea plume. The unexpected generation of these droplets has resulted in many studies in the last decade aiming to understand their transport and fate during and after the spill. Complicating matters, the plume coincided with a microbial bloom, and in addition to ocean dynamics these droplets were subjected to biological processes such as biodegradation and microbial aggregation. A lack of field observations and laboratory experiments using relevant conditions has left our understanding of these biotic processes and the role they played in the fate of the oil droplets poorly constrained. Furthermore, while biodegradation has been incorporated into drop transport models using available data, the effects of microbial aggregation involving extracellular polymeric substances (EPS) on their transport has seldom been incorporated into modeling efforts particularly due to our lack knowledge of these processes. We use a microfluidic platform to observe a bacterial suspension interacting with a 240 μm oil drop in conditions relevant to the drop rising through the microbial bloom. We observe the development of individual, practically invisible bacterial EPS threads extending from the drop surface which can capture additional passing bacteria and form bacteria-EPS aggregates. Using high speed imaging, we make high resolution flow measurements both with and without EPS threads present and analyze a momentum balance to elucidate the hydrodynamic impact of these threads. Surprisingly, these thin individual EPS threads cause a significant disturbance in the pressure field around the drop which in turn increases the drag which would drastically reduce the drops rising velocity in the water column. We demonstrate that this mechanism which plausibly occurred in the deep sea plume would have major impacts on both the drop and bacteria transport during and after the Deepwater Horizon oil spill.